The Hiroshima and Nagasaki Atomic Bombs: A Crossroads Between Ethics, Law and the Ambition of Victory - Ig Widi Nugroho; Danang Prasetyo W.; Tarsisius Susilo; Rahman Yadi; Joko Prasetyo (International Journal Labs, 2025)
The atomic bombings of Hiroshima and Nagasaki (1945) remain pivotal to debates on warfare ethics and international humanitarian law (IHL). Despite extensive historical analysis, gaps persist in reconciling these events with contemporary IHL frameworks and emerging technologies. This study evaluates the bombings’ compliance with IHL principles—distinction, proportionality, and prohibition of unnecessary suffering—and explores their relevance to modern conflict. A qualitative-descriptive, juridical-normative approach analyzes legal documents, historical archives, and hibakusha testimonies. The bombings violated core IHL principles, causing indiscriminate civilian harm (70,000–140,000 deaths) and prolonged suffering (radiation effects, hibakusha accounts). Legal justifications based on